Analysis of the LNG re-condensation system based on Joule-Thomson cooler. (April 2019) - Dorosz, P.; Piotrowska, A.; Pyrka, P.; Bogdan, P.
Abstract: Nowadays, LNG (Liquefied Natural Gas) has become a significant alternative fuel for both land and marine transport units. Due to formal regulations, gaseous natural gas (boil-off gas - BOG) cannot be released to environment when e.g. ship is docked or truck is out of operation. Stream of BOG can be burnt but this solution should be limited due to ecological reasons. Therefore, re-condensation systems allowing to extend holding time of the storage vessels are currently under strong interest and development. Joule-Thomson (J-T) cooler is simple cryogenic system, well recognized and tested. However, J-T coolers are not commercially available mainly because of very high working pressure and low thermodynamic efficiency. Both problems can be reduced by using gas mixture instead of single component working fluid. This paper presents thermodynamic analysis of the LNG re-condensation system based on Joule-Thomson cooler working in the closed system and supplied with gas mixture. Optimization analysis of the working mixture are presented. Theoretical results have been experimentally verified. Test results are presented and discussed.